A 27 years old Woman with Drug Reaction with Eosinophilic and Systemic Syndrome (DRESS) induced by 2nd Line treatment of Multi Drug Resistance Tuberculosis: A Case Report - Lucky Togihon Harjantho; Iin Noor Chozin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Drug Reaction with Eosinophilic and Systemic Syndrome (DRESS) also known as DrugInduced Hypersensitivity Syndrome initially recognized as a severe drug – induce hypersensitivity occurring2-8 weeks after drugs introduction.Case presentation: We report a 27 years-old woman treated by pyrazinamide, ethambutol, capreomycin,levofloxacin, cycloserine, and bedaquiline as an individual treatment for relaps multiple drug resistancepulmonary tuberculosis, then after eighteen days of treatment she admitted to our hospital because of hercomplaint about progressive skin rash, periodic fever, multiple lymphadenopathy, increased of eosinophiliacount, liver function test and renal function test. She have recovered after stopped the drugs and was givenof corticosteroids.Conclusion: Every patients with multi drug resistant (MDR) tuberculosis who receive 2nd line of MDRtuberculosis treatment have a possibility to develop DRESS. Giving of new individual treatment afterDRESS resolved, can lead to patient’s cure.